Effect of CFRP Sheets Strengthening Method on Behaviour of Modified Lightweight Foamed Concrete Beams - Angham Nassar Jaffal; Ameer A. Hilal; Akram S. Mahmoud (Journal of Engineering)
This study has been adopted to examine the effect of carbon fibre-reinforced polymer (CFRP) sheet strengthening methods on the flexural behaviour of modified foamed concrete beams reinforced with different steel reinforcement ratios, and it deals with the enhancement in flexural behaviour of conventional nonstrengthened FC beams. Twelve modified foamed concrete beams were produced in three groups depending on the reinforcement ratio (under, balanced and over) and strengthened with externally bonded CFRP sheets applied in different methods (bottom layer, U jacket and hybrid). The examined flexural variables in four-point bending were ultimate load, fracture mode, crack width, ductility, stiffness and deflection. The results showed an increase in the carrying capacity of foamed concrete beams strengthened with CFRP sheets by (2.5%–109%) compared to the reference nonstrengthened foamed concrete beams. The stiffness of the concrete samples reinforced with CFRP sheets were improved by 13%–306% compared to nonstrengthened foamed reference beams. For a given reinforcement ratio, it was found that the best CFRP sheets strengthening method was by applying the CFRP sheets in hybrid (wrap 0° + 90°).